Perbandingan Rest Api Menggunakan Node Js Dan Php Pada Aplikasi Pemilihan Umum - Haryadi, Habbyan Lazuard; Sujjada, Alun; Simatupang, Dwi Sartika (Jurasik (Jurnal Riset Sistem Informasi dan Teknik Informatika), 2023)
This study aims to analyze the comparison of the Representational State Transfer (REST) Application Programming Interface (API) between PHP and Node.js in the context of general election applications. The Prototype System Development Life Cycle (SDLC) method is used for application development. The performance of both programming languages is evaluated based on response speed, ease of development, and system capabilities. Data on Permanent Residents of Malang City with a total of 600 thousand data is used as a sample for database and server testing. The comparison results show that Node.js has a better response speed than PHP. However, PHP has an advantage in terms of ease of development. Both are able to handle applications with a large number of voters based on system capabilities. This research provides insight into the performance of PHP and Node.js in the context of REST API development for election applications